Optimum time for hand pollination in yam (Dioscorea spp.) - Mondo, J.; Agre, A.P.; Asiedu, R.; Akoroda, M.O.; Asfaw, A. (2022)
Hand pollination success rate is low in yam (Dioscorea spp.), due partly to suboptimal weather conditions. Thus, determining the most suitable time for pollination could improve the pollination success in yam breeding programs. We performed continuous hand pollination within flowering windows of D. rotundata and D. alata for two consecutive years to determine the most appropriate month, week, and hours of the day allowing maximum pollination success. In D. alata crossing block, we observed significant differences among crossing hours for pollination success (p = 0.003); morning hours (8–12 a.m.) being more conducive than afternoons (12–5 p.m.). No significant differences existed between crossing hours in D. rotundata, though the mid-day seemed optimal. For both species, the time interval 11–12 a.m. was more appropriate for crossing while 4–5 p.m. was the poorest. However, in vitro pollen germination tests showed that mid-day pollen collection (12 noon–2 p.m.) had better results than both extremes, though there were strong genotypic effects on outcomes. Pollination success rates differed significantly among months for D. alata (p < 0.001) but not for D. rotundata (p > 0.05). Differences in pollination success existed across weeks within flowering windows of both D. alata (p < 0.001) and D. rotundata (p = 0.004). The seed production efficiency (SPE) had a similar trend as the pollination success rate. No clear pattern existed between the pollination time and the seed setting rate (SSR) or seed viability (SV), though their dynamics varied with weeks and months. This study provided an insight on the dynamics of pollination outcomes under the influence of pollination times and allows detecting months, weeks, and hours of the day when hybridization activities should be focused for better results.